Volume equation for Populus deltoides plantation in western Terai of Nepal - Gautam, SK; Thapa, HB (Banko Janakari, 2009)
Allometric equations for estimating timber volume of Populus deltoides in plantation trial of Populus deltoides were developed. Direct measurement of 60 trees in western Nepal was done for this purpose. Six models were tested with simple linear regression analysis technique. The best fit equation for volume was quadratic (0.1500 - 0.0205DBH + 0.00105*DBH2) with diameter at breast height as an independent variable. Model recommended for estimating volume is based on diameter at breast height, because of the simplicity, easy to measure accurately in the field and the most common variable recorded in forest inventories. This model gave highest degree of determination (R2=0.88), and lowest standard error among the tested models. Keywords: Populus deltoids, volume, equation doi: 10.3126/banko.v17i2.2158 Banko Janakari, Vol. 17, No. 2, 70-73